Customer Service in Banks: Mapping Excellence in Emerging New Competitive Era - R. K. Uppal (Information Management and Business Review, 2011)
The Indian Banking Industry has undergone radical changes due to liberalization and globalization measures undertaken since 1991. Today, Indian Banking Industry is one of the largest in world. There has been a great surge in efficient customer services. A highly satisfied and delighted customer is a very vital nonfinancial asset for the banks in the emerging IT era. The curtsey, accuracy & speed are like a crown factors for a bank. Based on the responses of 768 customers of public sector bank, Indian Private Sector Bank & Foreign Bank (each one from these groups) operating in Amritsar district of Punjab and in case of fully E-bank, (three banks, one from each bank group) have been taken into consideration. It may be inferred that there is significant difference among three bank groups with regard to the time customers have to spend to transact a business. The E-banks are more efficient in regard to time factor. This is the very important factor of shifting of potential customers in E-banks. The survey was conducted in Amritsar district of Punjab in the month of September 2007. Chi-Square test is used to check the level of significance difference among various bank groups and coefficient of contingency among various bank group customers’ responses is also calculated.